The ledger and the chain : how domestic slave traders shaped America - Rothman, Joshua D. (Basic Books, 2021)
"In The Ledger and the Chain, prize-winning historian Joshua D. Rothman tells the disturbing story of the Franklin and Armfield company and the men who built it into the largest and most powerful slave trading company in the United States. In so doing, he reveals the central importance of the domestic slave trade to the development of American capitalism and the expansion of the American nation. Few slave traders were more successful than Isaac Franklin, John Armfield, and Rice Ballard, who ran Franklin and Armfield, and none were more influential. Drawing on source material from more than thirty archives in a dozen states, Rothman follows the three traders through their first meetings, the rise of their firm, and its eventual dissolution. Responsible for selling between 8,000 and 12,000 slaves from the Upper South to Deep South plantations over a period of eight years in the 1830s, they ran an extensive and innovative operation, with offices in New Orleans and Alexandria in Louisiana and Natchez in Mississippi. They advertised widely, borrowed heavily from bankers and other creditors, extended long term credit to their buyers, and had ships built to take slaves from Virginia down to New Orleans. Slavers are often misremembered as pariahs of more cultivated society, but as Rothman argues, the men who perpetrated the slave trade were respected members of prominent social and business communities and understood themselves as patriotic Americans. By tracing the lives and careers of the nation's most notorious slave traders, The Ledger and the Chain shows how their business skills and remorseless violence together made the malevolent entrepreneurialism of the slave trade. And it reveals how this horrific, ubiquitous trade in human beings shaped a growing nation and corrupted it in ways still powerfully felt today"--